A Nanoprobe for Diagnosing and Mapping Lymphatic Metastasis of Tumor Using 3D Multispectral Optoacoustic Tomography Owing to Aggregation/Deaggregation Induced Spectral Change. (9th January 2019) - Wu, Yinglong; Chen, Junjie; Sun, Lihe; Zeng, Fang; Wu, Shuizhu
Abstract: Lymphatic metastasis of tumor is one of leading causes of cancer‐related death, and diagnosing lymphatic metastasis is of significance in terms of optimal disease management and possible better outcomes for patients. Herein a turn‐on optoacoustic nanoprobe is reported for noninvasively diagnosing and locating lymphatic metastasis in vivo. A positively charged tricyanofuran‐containing polyene chromophore (TCHM) with high extinction coefficient is designed, synthesized, and allowed to form the nanoprobe with a negatively charged hyaluronan. The TCHMs take an aggregated state within the nanoprobe and exhibit weak absorption at 882 nm, the overexpressed hyaluronidase in cancer cells specifically degrades hyaluronan into small fragments and disaggregates TCHMs, thereby greatly enhancing the absorption at 882 nm and generating prominent optoacoustic signals. For multispectral optoacoustic tomography (MSOT) imaging in vivo, mice models with subcutaneous tumor and orthotopic bladder tumor are imaged first to demonstrate the nanoprobe's capability for detecting HAase‐overexpressing tumors. A mouse model of lymphatic metastasis of tumor is then established and the lymphatic metastasis is successfully imaged and tracked optoacoustically. The imaging results were verified using multiple biochemical assays. Moreover, 3D MSOT renderings are obtained for precisely locating and tracking the metastasis of tumor in lymphatic system in a spatiotemporal manner. Abstract : An activatable nanoprobe has been developed for noninvasively detecting lymphatic metastasis in a mouse model through multispectral optoacoustic tomography (MSOT) imaging. This probe can be used to diagnose orthotopic and metastatic tumors via responding to overexpressed hyalurodinase levels in tumors. With 3D MSOT images the metastatic route from primary tumor to sentinel lymph node via lymphatic vessel can be precisely mapped.